Percepções dos visitantes do Parque Ecológico de São Carlos sobre o papel dos zoológicos na conservação e Educação Ambiental - Silva, Isabela Vitor da (Universidade Federal de São Carlos, 2024)
Zoos constitute suitable spaces for the conservation of biological diversity and environmental education initiatives. However, there is still a significant challenge among the population in understanding the purposes of a zoo. This is due to the historical conception that animals are being used solely for entertainment. The present study aims to assess the perceptions of visitors to the "Dr. Antonio Teixeira Vianna" Ecological Park (PESC) regarding the role of zoos, especially this place situated in São Carlos (São Paulo - Brazil), as an educational space and a site for the conservation of fauna. Data acquisition was carried out through a questionnaire applied to visitors. The questionnaire included questions related to visitors' perceptions of PESC and the Environmental Education activities conducted there. Visitor responses were analyzed using qualitative and quantitative methods, including analysis performed with the IRAMUTEQ software. The results highlighted the importance visitors attribute to PESC as a location as close as possible to a natural ecosystem in the midst of the urbanized environmental, in addition to being a pleasant space for activities such as recreation. It was noted that there are various possibilities for improvements and the implementation of new activities that can further enhance the role of PESC as an educational space and facilitate closer contact with animals, complementing the existing activities. In addition to the fact that the present study can assist in the planning of other Environmental Education activities in the PESC, it is suggested that such actions should t be based on a more critical and emancipatory approach to Environmental Education.
Perceptions of São Carlos Ecological Park visitors about the role of zoos in conservation and Environmental Education
Keywords: Conservação ex situ; Espaço educador; Percepção ambiental; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO